MANAJEMEN RESIKO PADA PENGOLAHAN PEMINDANGAN IKAN DI DESA SANDING ROWO SOKO TUBAN - Siti Nuriya Kartika Ningrum; Dewi Rochmayanti; Risma Cahyani; Vika Dwi Indriani (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to identify internal and external factors that affect the risks faced by the income earned in the fish farming business in Sanding Rowo Soko Tuban Village. The research method used is descriptive quantitative with a population and the research sample is a fish farming business actor totaling 10 people. Technical analysis uses business income analysis by calculating the difference between receipts and expenses. The risk analysis is analyzed using the method of expected results (E) and the magnitude of risk (V). The results showed that the income earned by fish farming entrepreneurs was Rp. 3,728,908/week. With a variation coefficient (CV) value of 0.03 with a lower limit value of income (L) of Rp. 3,135,080 / week, so that fish farming entrepreneurs always have the opportunity to make a profit in every fish harvesting process.